Division of joint assets according to Dayak Kenyah customary law after a divorce occurs in terms of law number 1 of 1974 - Fransiska Wendy Wijaya (Requisitoire Law Enforcement, 2022)
In this research, the author tries to explore how the division of common property is carried out according to Dayak Kenyah Customary Law due to one of the causes of marriage breakdown, namely divorce caused by the death of one of the parties or divorce love; caused by the wishes of both parties; caused by one of the parties having an affair or divorce cek cok and how the implementation of decisions that have been determined by the Customary Institution. The research method used is anthropological juridical by examining the realities that exist and apply in the Dayak Kenyah customary society related to the division of joint property after divorce and literature study of data from previous research and Law No. 1 of 1974. The result of this research related to the issue of division of joint property according to Dayak Kenyah Customary Law after divorce is that joint property absolutely belongs to the party declared innocent by the Customary Institution if the cause of the divorce is one of the parties having an affair or divorce caused by the death of one of the parties. As for divorce caused by the wishes of both parties, then the joint property is divided in half. The implementation of the decision stipulated by the Customary Institution is mandatory but there are still some of the Dayak Kenyah indigenous people who do not want to implement the decision and this is related to the beliefs or religion adopted by the Dayak Kenyah indigenous people so that pros and cons arise in the indigenous community itself.